Trends of pH and aerosols in the precipitation at Srinagar, Mohanbari, Allahabad, Jodhpur, Nagpur and Minicoy during the period 1981-2001 - TOMAR, M.S. (MAUSAM, 2011)
Nature of Precipitation - alkaline or acidic depends upon the concentration of major water soluble inorganic gaseous and soil derived particulates dissolved in it. If the concentration of cations is higher than that of anions the precipitations becomes alkaline and vice versa. pH is the main parameter indicating the nature of precipitation. If pH of rainwater <5.65 it is acidic and >5.65, it is alkaline ,both in the pH scale ranging between 0 and 14. In this paper average ionic concentration (mg/lit) and their trends have been analyzed. Srinagar, Mohanbari, Jodhpur, Allahabad, Nagpur and Minicoy have been selected for the study of chemical precipitation during the period 1981-2001. Trends of different aerosols have been analyzed at the intervals 1981-87, 1988-94 and 1995-2001. It has been observed that percentage of anions has increased which results in the increase of acidic character of the precipitation. During the interval 1995-2001, Nagpur and Mohanbari had pH values 5.16 and 5.47 respectively which were in acidic range.